A Novel Mg-Al-Co LDH/ MAO Composite Films on LA103Z Magnesium-Lithium Alloy and Its Active Anti-corrosion Performance. Issue 4 (2nd October 2021) - Zhang, Jumei; Wang, Kai; Duan, Xin; Hou, Anrong; Li, Jiacheng; Cai, Hui; Wang, Zhihu
Abstract : In order to further improve the corrosion resistance of the micro-arc oxidization (MAO) film on LA103Z magnesium-lithium alloy, a Mg-Al-Co layered double hydroxide (LDH) film was fabricated on MAO film by an in-situ hydrothermal method. The results showed that with the extension of hydrothermal treatment time, the dense LDH film sealed the micro-pores and cracks in the MAO film successfully. In addition, LDH film treated with a hydrothermal treatment at 90°C for 24 h has the best electrical insulation. The hydrogen evolution rates (mL.cm –2 .h −1 ) of the LDH/MAO composite films rank as LDH/MAO-24 h ≈ LDH/MAO-30 h (0.12) < LDH/MAO-18 h (0.15) < LDH/MAO-12 h (0.16) < MAO (0.25). Meanwhile, the results of potentiodynamic polarization curves showed that the corrosion potential of LDH/MAO-24 h film increased from –1.5349 to −1.388 V, and the corrosion current density decreased by three orders of magnitude. Therefore, the LDH/MAO film has better corrosion resistance than a single MAO film and adds long-term corrosion resistance to the magnesium alloy, which owes to the sealing effect of LDH on inherent defects and trapping effect on corrosion ions. GRAPHICAL ABSTRACT: UF0001